Homes for workers, 1945 (1945)
1945 1939-1945 "Homes for workers, 1945" [HFR0111], 1945 In the post war period, Britain faced a housing crisis due to the loss or damage to millions of homes plus a shortage of building materials. This article is from Challenge, the weekly newspaper of the Young Communist League.